The ends of satire : legacies of satire in postwar German writing - Bowles, Daniel James, 1981- (Paradigms-- Literature and the human sciences ;, 2015)
"How are we to think of satire if it has ceased to exist as a discrete genre? This study proposes a novel solution, understanding the satiric in the postwar era as a set of writing practices: figures of inversion, myth-making, and citation. By showing how writers and theorists alike deploy these devices in new contexts, this book reexamines the link between German postwar writing and the history of satire, and between literature and theory." --